PENGARUH LATIHAN BEANBAG RELAYTERHADAPKECEPATAN LARI JARAK PENDEK 100 METER PADAATLET ATLETIK PUTRA PPLP RIAU - Muhammad sukri sukri; Ramadi '; Kristi Agust Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrac, This research was conducted to find out whether there was an influence of beanbag relay exercises toward speed of 100 meters sprint on men athelete athletic of PPLP Riau. The data In this research was an experimental, The total number of athletes in this research 6 people. The Instruments which have done in this research was the 100 meter sprint speed test which was aims to measure speed. Then, the data processed with statistic, to normalitas test with lilieforrs test on significan extent Alfa = 0,05, the hypothesis put forward there was influence of beanbag relay exercise toward speed of 100 meters sprint on athlete athletic of PPLP Riau.Based on the analysis of the t test found the t obtain was 3.166 and t table 2.015 means t obtain > t table. Based on the mean score of pre test was 6.64 test and the mean score of post test was 6.83 and based on t- test after calculated there was difference numbers that increase or increasing with mean score 0.972. From the explanation above can be concluded, there was the influence of beanbag relay exercise to ward of speed 100 meters sprint on athlete athletics PPLP Riau . Keywords : Beanbag Relay Excercise Toward Speed of 100 Meters Sprint on Men Athletes Athletic in PPLP Riau.